Refresentasi Perempuan Maskulin Dalam Film - Pandu Satya Yudha; Siti Komsiah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This research discusses about of the representation female masculinity in vengeance is mineall others pay cash Film, using Semiotic analysis Roland Barthes. As the purpose of this researchis to find out a denotation, connotation, adn myth meaning of female masculinity in vengeance ismine all others pay cash Film. This research is also using social construction theory from Bergerand Luckman. Then, such a concept like communication, mass communication, movie, andmeaning. This research uses a qualitative approach, using semiotic method, and descriptivequalitative as type of research. Data collection techniques used are observation, literature study,and other source. As well as data validity technique through triangulation of methods andtrianglation theory. The results of this study, there is denotation meaning, connotation meaning,myth and a women masculinity representation that shows by Iteung, and Jelita where ther shows awomen masculinity charahcters and theres nothing wrong to have a masculine nature even a genderis women. Because so far women is get costructed by society is to be feminine. By socialconstruction, vengeance is mine all others pay cash Film could make a reality that a women is notalways to be feminine, but a women could be masculinity